An instrument for measuring the degree of lean implementation in manufacturing - Vujica-Herzog, Nataša (Strojniški vestnik, 2014)
Despite lean thinking being a broadly accepted approach, there is still some confusion within present terminology regarding 'lean' and its issues. This paper presents the results of a research survey carried out within 72 medium and large-sized Slovenian manufacturing companies. The sample selection criteria adopted, together with the research items investigated, ensured a generic framework for our research. Eight crucial areas were identified based on a synthesis of 'lean' literature for assessing and measuring the degree of lean implementation within existing manufacturing systems: value concept and customers, value stream mapping (VSM), pull/kanban and flow, waste elimination, productive maintenance, just-in-time (JIT), employee involvement and the development of excellent suppliers (lean suppliers). Variables were constructed within these areas using Likert scales, and statistical validity and reliability analyses. For example, when measuring the developments of excellent suppliers the focus should be on three variables: on time deliveries, supplier relationships, and a skilled and loyal supplier. The results show that the developed variables can be important both for understanding 'lean' and measuring the degree of lean implementation within existing manufacturing systems.
Keywords: anketne raziskave; merjenje izvedbe; oblikovanje novih spremenljivk; veljavnost; vitka proizvodnja; zanesljivost